Structure of benthic communities in small rivers of southern Sakhalin in summer-autumn period, a case of the Lyutoga River tributaries - Lyubov A. Zhivoglyadova; Vyacheslav S. Labay; Dinara S. Dairova; Irina V. Motylkova; Vitaly D. Nikitin; Alexandra V. Polteva; Elena V. Galanina (Известия ТИНРО, 2016)
Quantitative characteristics of microbial community, algal periphyton and macrozoobenthos are presented for two tributaries of the Lyutoga River, as the Partizanka River (pink salmon spawning stream) and the Frikena River (without steady spawning grounds), on the base of surveys conducted in July-October, 2011. Number of benthic bacteria in the bottom grounds varied in the range 1.1-4.0 · 106 cells/g in the Frikena and 0.8-11.1 · 106 cells/g in the Partizanka. Oligocarbophilic microorganisms prevailed in the bacterial benthos of both rivers before the beginning of active salmon spawning (July- August), developing mainly on autochthonous organic substrates. In September, with appearance of salmon carcasses after spawning, total abundance of the microorganisms increased and the portion of ammonifying bacteria basing on this allochthonous organic matter became higher in the Partizanka. Algal periphyton biomass changed from 7.8 to 117.0 g/m2 in the Frikena River and from 0.5 to 305.6 g/m2 in the Partizanka River, with diatoms domination in both streams. Periphyton in the Partizanka was destroyed by flood in September but successively recovered by October, with multiple increasing of the algal biomass, obviously due to influx of nutrients in the process of salmon carcasses decomposing. Biomass of macrozoobenthos was 5.1-21.0 g/m2 in the Frikena River and 2.2 to 3.7 g/m2 in the Partizanka River, in both tributaries its dynamics was determined mainly by life cycles of aquatic insects.